Results Of The Combined Use Of A Phascocidium Drug And An Immunoparasitic Immunostimulator In Dewormintization Of Cattle. - Kunisov Bao'irjan; Abdiyeva Tursinay; Saburov Alisher; Yerniyazov AlKidirniyaziybay; Kaipbergenov Kamal (Genius Journals, 2024)
For the treatment and prevention of fascioliosis in the liver, immunocorrective roncholeukin is used in combination with antitheloid fasciocid. Over the course of our experiment, drug efficacy (fascocid + immunoparasitic) is 5.3% more effective and reduces the level of invasion extensibility (IE) by 98.3%, the intensity of invasion (II) by 92.5%, the known method reduces the level of invasion extensibility (IE) by 93%, and the intensity of invasion (II) by 85.2%.
Keywords: fascioliasis; fasciocid; immunoparasite